MALARIA IN PREGNANCY WAD MEDANI MATERNITY TEACHING HOSPITAL - Miskeen, Elhadi Ibrahim; Ahmed Mirghani, Omer (Gezira Journal of Health Sciences, 2006)
This is a prospective hospital - base study conducted in Wad Medani Maternity Teaching Hospital, during the period from 5 th of October 2003 to 30 th of December 2003. The objectives of this study were to assess the status of malaria in the wards in Wad Madani Maternity Teaching Hospital, to determine the effects of malaria on the mother as well as on pregnancy outcome, and also to test the National Protocol for Treatment of Malaria during Pregnancy using Wad Madani Maternity Teaching Hospital.  Methodology: All pregnant women with malaria admitted to the hospital during that period were included in the study. Malaria was diagnosed by thick and thin blood film, Gimsa’s stain. Severe falciparum malaria was diagnosed according to WHO criteria. NationalProtocol for Treatment of Malaria during Pregnancy was adopted in the management of all women. Patients were consider to be cure if symptoms and signs disappeared. The results were analyzed using SPSS. The total number of pregnant women included in this study was 210. The main results of the study were: (i) severe falciparum malaria (73.4%), (ii) anaemia (98.6%) of whom 20%) was severe and (11 %) was very severe, (iii) hyperparasitaemia (46.7%), (iv) dehydration (33.3%) and (v) jaundice (20.5%). Complications on the fetus were: (i) preterm labour (44.1 %), (ii) low Agar’s score < 7 (55.9%), (iii) low weight < 2.5 (44.1 %) and (iv) perinatal death (5.5%). Quinine was the main drugs used. Conclusion: Pregnant women admitted to the hospital need intensive care. Although there was no mortality but morbidity was high. The current protocol is adequate in reducing mortality. Intervention to reduce poor pregnancy outcomes must reduce the burden of malaria in pregnancy.